Legal Discovery Method for Non-Muslim Heirs as Recipients of Wasiat Wajibah - Ramdan Fawzi; Encep Abdul Rojak; Ilham Mujahid; Mualimin Mochammad Sahid (Faculty of Sharia - Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Non-Indexed Publication